(untitled) (Research, Society and Development, 2022)
The mineral processing of friable iron ores usually generates ultrafine (smaller than 15 µm) particles, normally called slimes, which usually have a high iron grade and are usually disposed into tailings dam. The traditional mineral process techniques for iron ore do not work efficiently with ultrafines; however, selective flocculation is an alternative to concentrate that fraction. The physical-chemical treatment of iron ore slime was studied here, on a bench scale, based on the scientific foundations of selective flocculation and flotation. Samples of slimes from two Brazilian iron ore processing plants (CEII and VGII) and industrial process waters were used in the tests. Complexometric titration of calcium and magnesium indicated that the process waters were adequate for selective flocculation. Only selective flocculation, even under optimum conditions, did not achieve good results. However, its use prior to flotation led to promising results. The VGII sample has stood out, for which the final concentrate achieved 60.1 % of Fe, the mass recovery was 64.5 % and 13.5 % of Fe in the tailing, resulting selectivity index of 6.58, only with one stage of selective flocculation and one stage of flotation.